IMPLEMENTATION OF KEEP ON LEARNING STRATEGY TO IMPROVE STUDENT LEARNING OUTCOMES IN SCIENCE SUBJECTS CLASS IV STATE ELEMENTARY SCHOOL 142 BENGKULU UTARA - Watini; Azmi , Ulil (PT. Antis International Publisher, 2024)
Objective: This study examines the implementation of the